Italia di mezzo: The emerging marginality of intermediate territories between metropolises and inner areas - Francesco Curci; Agim Kërçuku; Arturo Lanzani; Federico Zanfi (REGION, 2023)
The Italian debate concerning the relationship between cities and inner areas polarized around a few dichotomous - and somehow simplifying - positions. On the one hand exists the rhetoric addressing the ''villages'', intended as remote places to re-inhabit, escaping from the pandemic. On the other hand is the narrative of the metropolis, envisioned as a place-fulcrum from which to start again – following the already-known patterns of growth and concentration – despite the fragilities made explicit by Covid. In order to overcome these juxtaposed approaches, our work wants to shed light on the importance of ''intermediate territories'' intended as priority places to rethink within a new geography of marginality. In Italy, such intermediate territories, named Italia di mezzo, occupy half of the national surface and host more than half of the population. Moreover, they embody extremely articulated geography: they include portions of twentieth-century urbanization (such as coastal settlements, industrial districts, various traits of ''città diffusa''), medium-sized cities with different administrative and functional centrality levels, sectors of metropolitan belts and a substantial share of rural areas in plains and hills. Faced with the radical risks and uncertainties that characterize the contemporary condition, it is essential to take care of these territories not only because they urgently need investments aimed at solving forgotten critical issues (from the necessary reconversion of production chains to the impact of climate change). These territories can also play a strategic positive role in the face of crisis phenomena thanks to their characteristics of elasticity and plasticity. If we look at them from a relational point of view - and not only from a topological one - these intermediate territories can play the role of two-sided ''intermediaries'' and ''hinges.'' On the one hand, they can be prepared to provide assistance and support to the inner and less densely populated areas; on the other hand, by taking advantage of their infrastructural and social capital, they can offer decongesting opportunities for most polluted metropolitan areas and more accessible living and working conditions.
Keywords: 330